Evaluasi Konsumsi Air Beberapa Genotipe Padi untuk Potensi Efisiensi Penggunaan Air - , Supijatno; Muhammad Ahmad Chozin; Didy Sopandie; , Trikoesoemaningtyas; Ahmad Junaedi; Iskandar Lubis (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2012)
Water use efficient varieties in rice may have good opportunity in term of economic value and scarcity of water. This study was conducted to determine water consumption among rice genotypes that conventionally cultivated as low land (IR64, IPB97-F-15, Ciherang, Mentik Wangi, and Rokan hybrid), up land (Jatiluhur, Silugonggo), and amphibian type (Way Apo Buru, that could be planted both as lowland and up land). Rice seedlings at 14 days old were transplanted in a plastic container containing 83 kg of air dried soil, 1 plant per whole and 6 plants per container. The experiment was conducted in a vinyl house, using randomized complete block design with three replications. During rice growth, water table was maintained at 2 cm above soil surface, and water was added and recorded weekly. The results showed that varieties reveal production components and yield were different significantly. Water consumptions among varieties were significantly different, ranged from 15.93 L plant-1 for IR64 to 24.13 L plant-1 for Jatiluhur, or equal with 3,639 to 4,827 m3 ha-1. Jatiluhur was the most efficient variety in using water. This finding may guide us to explore benefit of water use efficient variety as sustainable option in water management of rice cultivation.